One‐dimensional metal–organic framework‐reinforced gel polymer electrolyte enables a stable Li metal battery. Issue 4 (25th March 2022) - Shi, Rongjia; Liao, Kaiming; Wang, Cuie
Abstract: Gel polymer electrolytes (GPEs) are intrinsically advantageous over rigid inorganic ones due to their easy processability and scalability. However, in terms of poor mechanical strength, GPEs can hardly satisfy the requirement of practical Li metal batteries. Herein, a novel one‐dimensional Cu‐metal–organic framework (MOF)‐filler‐reinforced GPE with the merits of high mechanical strength and high ionic conductivity is developed. When such GPE is used in Li symmetrical cells, small and stable Li‐plating/stripping overpotentials (~50 mV) can be maintained over 350 h at .3 mA/cm 2 . Benefitting from the above MOF‐filler‐reinforced GPE, a full cell with the Li metal anode and LiFePO4 cathode presents a stable cycling performance with a low capacity decay rate of .004% per cycle over 800 cycles at 1 C.